Investigation of potential waste material insulating properties at different temperature for thermal storage application - T. Z. S., Ali; R. A., Bakar; Gan, Leong Ming; Billy, Anak Sup; Farid, Z. (IOP Publishing, 2013)
Thermal energy storage system (TES) is developed to extend the operation of power generation. TES system is a key component in a solar energy power generation plant, but the main issue in designing the TES system is its thermal capacity of storage materials, e.g. insulator. This study is focusing on the potential waste material acts as an insulator for thermal energy storage applications. As the insulator is used to absorb heat, it is needed to find suitable material for energy conversion and at the same time reduce the waste generation. Thus, a small-scale experimental testing of natural cooling process of an insulated tank within a confined room is conducted. The experiment is repeated by changing the insulator from the potential waste material and also by changing the heat transfer fluid (HTF). The analysis presented the relationship between heat loss and the reserved period by the insulator. The results show the percentage of period of the insulated tank withstands compared to tank insulated by foam, e.g. newspaper reserved the period of 84.6% as much as foam insulated tank to withstand the heat transfer of cooking oil to the surrounding. The paper finally justifies the most potential waste material as an insulator for different temperature range of heat transfer fluid.